Description of the female of Labena madoricola González-Moreno & Bordera, 2015 (Hymenoptera, Ichneumonidae, Labeninae), with new records of Labena species from Mexico - González-Moreno, Alejandra; Bordera, Santiago (Zootaxa, 2017)
The female of Labena madoricola González-Moreno & Bordera, 2015 is described and illustrated for the first time from material collected with Malaise traps in 2016 in the Biocultural Reserve Kaxil Kiuic, Yucatán, Mexico. Diagnostic characters to distinguish females of New World Labena are provided. New distribution records of Labena species in Yucatán Peninsula, are also reported.